Gender and Genre in the Folklore of Middle India - Flueckiger, Joyce Burkhalter (Myth and Poetics, 1996)
In Gender and Genre in the Folklore of Middle India, Joyce Burkhalter Flueckiger analyzes six representative Indian folklore genres from a single regional repertoire to show the influence of their intertextual relations on the composition and interpretation of artistic performance. Placing special emphasis on women's rituals, she looks at the relationship between the framework and organization of indigenous genres and the reception of folklore performance. The regional repertoire under examination presents a strikingly female-centered world. Female performers and characters are active, articulate, and frequently challenge or defy expectations of gender. Men also confound traditional gender roles. Flueckiger includes the translations of two full performance texts of narratives sung by female and male storytellers respectively.